Efficacy of Bay Leaf (Syzygium polyanthum) Decoction in Managing Type 2 Diabetes Mellitus Patients: A Randomized Controlled Trial - Kurniawati, Erna Yovi; Muhlida, Vinilia Ihramatul; Dewi, Mariza Mustika; Margiyati (Al-Hijrah Indonesia, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycaemia, leading to complications such as cardiovascular disease and kidney failure. The increasing prevalence of T2DM necessitates effective management strategies, including complementary therapies like bay leaf (Syzygium polyanthum), which has demonstrated potential for glycaemic control. Purpose: This study aimed to evaluate the effectiveness of bay leaf decoction in improving glycaemic control among T2DM patients in Malangan Village. Methods: A randomized controlled trial (RCT) involved 60 adults aged 30-65 years with fasting blood sugar (FBS) levels between 126-200 mg/dL, selected through purposive sampling. Participants were randomly assigned to an intervention group receiving a bay leaf decoction (10 grams in 250 mL water, twice daily for 12 weeks) or a control group receiving a placebo decoction. Primary outcomes included changes in FBS, while secondary outcomes assessed postprandial blood sugar (PBS) and HbA1c. Compliance and adverse events were monitored, and data were analysed using paired and independent t-tests (p < 0.05). Results: The intervention group showed significant reductions in FBS, PBS, and HbA1c levels compared to the control group (p < 0.05). Older age, female gender, and higher education correlated with improved glycaemic control, while obesity and hypertension were associated with poorer outcomes. No severe adverse events were reported. Conclusion: Bay leaf decoction significantly improves glycaemic control through mechanisms such as enhanced insulin sensitivity, α-glucosidase inhibition, and antioxidant properties. This natural, cost-effective approach is promising as a complementary therapy for T2DM. Future research should explore long-term effects, optimal dosage, and integration with lifestyle interventions to maximize benefits.